Antibacterial and osteogenesis performances of LL37-loaded titania nanopores in vitro and in vivo - Shen X (Dove Medical Press, 2019)
Xinkun Shen,1 Mohammed A Al-Baadani,1 Hongli He,1 Lina Cai,1 Zuosu Wu,1 Litao Yao,1 Xinghai Wu,1 Shuyi Wu,1 Mengyu Chen,1 Hualin Zhang,2,3 Jinsong Liu11School and Hospital of Stomatology, Wenzhou Medical University, Wenzhou 325027, People’s Republic of China; 2College of Stomatology, Ningxia Medical University, Yinchuan 750004, People’s Republic of China; 3General Hospital of Ningxia Medical University, Yinchuan 750004, People’s Republic of ChinaBackground: Many studies have shown that the size of nanotube (NT) can significantly affect the behavior of osteoblasts on titanium-based materials. But the weak bonding strength between NT and substrate greatly limits their application.Purpose: The objective of this study was to compare the stability of NT and nanopore (NP) coatings, and further prepare antibacterial titanium-based materials by loading LL37 peptide in NP structures.Methods: The adhesion strength of NT and NP layers was investigated using a scratch tester. The proliferation and differentiation of MC3T3-E1 cells on different substrates were evaluated in vitro by CCK8, alkaline phosphatase activity, mineralization and polymerase chain reaction assays. The antibacterial rates of NP and NP/LL37 were also measured by spread plate method. Moreover, the osteogenesis around NP and NP/LL373 in vivo was further evaluated using uninfected and infected models.Results: Scratch test proved that the NP layers had stronger bonding strength with the substrates due to their continuous pore structures and thicker pipe walls than the independent NT structures. In vitro, cell results showed that MC3T3-E1 cells on NP substrates had better early adhesion, spreading and osteogenic differentiation than those of NT group. In addition, based on the drug reservoir characteristics of porous materials, the NP substrates were also used to load antibacterial LL37 peptide. After loading LL37, the antibacterial and osteogenic induction abilities of NP were further improved, thus significantly promoting osteogenesis in both uninfected and infected models.Conclusion: We determined that the NP layers had stronger bonding strength than NT structures, and the corresponding NP materials might be more suitable than NT for preparing drug-device combined titanium implants for bone injury treatment.Keywords: titanium, nanotubes, nanopores, LL37 peptide, antibacterial, osteogenesis